Paget's disease of the vulva: clinicopathologic study of type 1 cases treated at a single institution. Issue 3 (1st April 2006) - Niikura, H.; Yoshida, H.; Ito, K.; Takano, T.; Watanabe, H.; Aiba, S.; Yaegashi, N.
Abstract : The aim of this study was to evaluate clinicopathologic characteristics of primary cutaneous Paget's disease of the vulva. Between 1986 and 2005, 22 patients with primary cutaneous Paget's disease of the vulva (type 1) were treated at Tohoku University Hospital. Medical records were reviewed for pathologic diagnosis, patient age, associated neoplasms, type(s) of eczema, symptom duration, treatment, surgical procedures, recurrence, and length of follow-up. Patient age ranged from 51 to 85 years (median 71.5 years). Median duration of symptoms was 24 months (range 2–60 months). Type 1a (intraepithelial) Paget's disease accounted for 18 patients, with 3 type 1b (invasive) cases and 1 type 1c (intraepithelial disease with underlying adenocarcinoma) case. Mean length of follow-up was 53.7 months, and median follow-up was 49 months (range 6–199 months). Only two patients had an associated internal malignancy: T-cell leukemia and breast cancer. Mapping biopsy was performed in 14 of the 18 type 1a cases. All patients were free of disease at the surgical margins and are alive without recurrence. The four patients with type 1b or 1c disease had lymph node metastases. Two has died of disease, and two are alive with no recurrence. The rate of secondary malignancy seems to be low in primary cutaneous Paget's disease of the vulva. Mapping biopsy with careful examination of characteristic skin surface may be useful for surgery of type 1a cases. Inguinal lymphadenectomy is recommended in cases with question of invasion or known underlying adenocarcinoma.